Intervention Now To Eliminate Repeat Unintended Pregnancy in Teenagers (INTERUPT): a systematic review of intervention effectiveness and cost-effectiveness, qualitative and realist synthesis of implementation factors and user engagement. Issue 4 (10th April 2014) - Whitaker, Rh; Hendry, M; Booth, A; Carter, B; Charles, J; Craine, N; Edwards, R T; Lyons, M; Noyes, J; Pasterfield, D; Rycroft-Malone, J; Williams, N
Abstract : Background: The UK has the highest rate of teenage pregnancies in Western Europe, a fifth are repeat pregnancies. Unintended conceptions can result in emotional, psychological and educational harm to teenage girls, often with enduring implications for their life chances. Babies of teenage mothers have increased mortality in their first year and increased risk of poverty, educational underachievement and unemployment later in life, with associated societal costs. Methods and analysis: We will conduct a streamed, mixed-methods systematic review to find and evaluate interventions designed to reduce repeat unintended teen pregnancies. Our aims are to identify: Who is at greater risk of repeat unintended pregnancies? Which interventions are effective, cost-effective, how they work, in what setting and for whom? What are the barriers and facilitators to intervention uptake? Traditional electronic database searches will be augmented by targeted searches for evidence 'clusters' and guided by an advisory group of experts and stakeholders. To address the topic's inherent complexities, we will use a highly structured, innovative and iterative approach combining methodological techniques tailored to each stream of evidence. Quantitative data will be synthesised with reference to Cochrane guidelines for public health interventions. Qualitative evidence addressing facilitators and barriers to the uptake of interventions, experience and acceptability of interventions will be synthesised thematically. We will apply the principles of realist synthesis to uncover theories and mechanisms underpinning interventions. We will conduct an integration and overarching narrative of findings authenticated by client group feedback. Ethics and dissemination: We will publish the complete review in 'Health Technology Assessment' and sections in specialist peer-reviewed journals. We will present at national and international conferences in the fields of public health, reproductive medicine and review methodology. Findings will be fed back to service users and practitioners via workshops run by the partner collaborators. Trail registration number: PROSPERO CRD42012003168. Cochrane registration number: i=fertility/0068.